a x − 2 2 4 x 2 + 2 5 x − 4 7 = − 8 x − 3 − a x − 2 5 3
The equation above holds true for all values of x = a 2 , where a is a constant. What is the value of a ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
a x − 2 2 4 x 2 + 2 5 x − 4 7 = − 8 x − 3 − a x − 2 5 3
⟹ 2 4 x 2 + 2 5 x − 4 7 = − 8 x ( a x − 2 ) − 3 ( a x − 2 ) − 5 3
⟹ 2 4 x 2 + 2 5 x − 4 7 = − 8 a x 2 + 1 6 x − 3 a x + 6 − 5 3
⟹ 2 4 x 2 + 2 5 x − 4 7 = − 8 a x 2 + 1 6 x − 3 a x − 4 7
⟹ 2 4 x 2 + 2 5 x = − 8 a x 2 + 1 6 x − 3 a x
⟹ x ( 2 4 x + 2 5 ) = x ( − 8 a x + 1 6 − 3 a )
⟹ ( 2 4 x + 2 5 ) = ( − 8 a x + 1 6 − 3 a )
⟹ 2 4 x + 9 = − 8 a x − 3 a = − a ( 8 x + 3 )
⟹ 3 ( 8 x + 3 ) = − a ( 8 x + 3 )
⟹ 3 = − a
⟹ a = − 3
Great Solution
I did the same thing. Nicely done, and well presented LaTeX! +1
There are two ways to solve this question. The faster way is to multiply each side of the given equation by ax−2 (so you can get rid of the fraction). When you multiply each side by ax−2, you should have: 2 4 x 2 + 2 5 x − 4 7 ==(−8x−3)(ax−2)−53 You should then multiply (−8x−3) and (ax−2) . 2 4 x 2 + 2 5 x − 4 7 =−8ax^2−3ax+16x+6−53 Then, reduce on the right side of the equation 2 4 x 2 + 2 5 x − 4 7 =−8ax^2−3ax+16x−47 Since the coefficients of the x^2-term have to be equal on both sides of the equation, −8a=24, or a=−3.
Comparing coefficients of x 2 on both sides of the equation we get − 8 a = 2 4 ⟹ a = − 3 .
Yes, correct
Problem Loading...
Note Loading...
Set Loading...
a x − 2 2 4 x 2 + 2 5 x − 4 7 a x − 2 2 4 x 2 + 2 5 x + 6 − 5 3 a x − 2 2 4 x 2 + 2 5 x + 6 − a x − 2 5 3 ⟹ 2 4 x 2 + 2 5 x + 6 ⟹ a = − 8 x − 3 − a x − 2 5 3 = − 8 x − 3 − a x − 2 5 3 = − 8 x − 3 − a x − 2 5 3 = ( − 8 x − 3 ) ( a x − 2 ) = − 3